The Mediterranean Between Myth and History - Motta, Giovanna (Richtmann Publishing, 2010)
The purpose of this article is to analyze the Mediterranean as an aquatic area that for centuries has united different people and cultures together in one story. The methodology consists of the analysis of historical documents of the different archives in west Europe, that shows complex stories with witch connect ancient links of the East. The long transition from feudalism to capitalism represents the background for the action of important personalities, that for the realization of their political and military projects confront themselves with other players and the enemy par excellence, represented by the Ottoman Empire. The War is an integral part of the society of the old regime, both for the conquest and the defense and, in this framework, it is extremely useful to reveal the story of important leaders, such as Mattia Corvino, Scanderbeg and many other on the eastern quadrant, which outlines the traits of Mediterranean where there are not only factors of unification, but also issues of division. Migration, with the cultures that bring, it fits into the larger context of the national heritage of different people, which remain in the literature and poetry, music, dance, a wealth of great significance attesting ancient cultural mergers that introduces imagination and memories of all. In this prospect, as in other cases, including war, it gave rise to occasions that have consented different people to build a great deal of a common history.